Predicting the Mental Health and Functioning of Torture Survivors. Issue 1 (January 2018) - Song, Suzan J.; Subica, Andrew; Kaplan, Charles; Tol, Wietse; de Jong, Joop
Abstract : Abstract: The psychological effects of war represent a growing public health concern as more refugees and asylum seekers migrate across borders. This study investigates whether sociodemographic, premigration and postmigration, and psychosocial factors predict adverse psychiatric symptoms in refugees and asylum seekers exposed to torture ( N = 278). Hierarchical linear regressions revealed that female sex, older age, and unstable housing predicted greater severity of anxiety, posttraumatic stress disorder (PTSD), and depression. Cumulative exposure to multiple torture types predicted anxiety and PTSD, while mental health, basic resources (access to food, shelter, medical care), and external risks (risk of being victimized at home, community, work, school) were the strongest psychosocial predictors of anxiety, PTSD, and depression. Also, time spent in the United States before presenting for services significantly predicted anxiety, PTSD, and depression. Consequently, public-sector services should seek to engage this high-risk population immediately upon resettlement into the host country using a mental health stepped care approach.